PENGEMBANGAN LESSON DESIGN SHARING & JUMPING TASKS UNTUK MENUMBUHKAN AKTIVITAS KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN REAKSI REDOKS - Yunita Danora, - (2020)
This study aimed to develop a lesson design of sharing & jumping tasks that can foster students' critical thinking skills activities in learning redox reaction. The research method used was developmental research with Didactical Design Research (DDR). It consist of three stages, namely prospective analysis, metapedadidactic analysis, and retrospective analysis. The developed lesson design was implemented at class X MIA (Sciences and Mathematics) at a senior high school in Bandung. Data were collected through learning observation, teachers' interview, document studies and recordings (audio and video). The lesson design of sharing & jumping tasks on redox reaction topic consisted of three learnings stages, namely opening, main activities (sharing task 1, sharing task 2, jumping tasks), and closing. The result of students' critical thinking skill activities analysis based on Transcript Based Lesson Analysis (TBLA) indicated that the implementation of lesson design sharing & jumping tasks on redox reaction topic could foster the students' critical thinking skill activities during the learning process. Based on Ennis' critical thinking indicators (1985), there were 11 indicators with students' highest critical thinking activity of 80.8%. In sharing task 1, there were 11 indicators with students' highest critical thinking activity of 61.5%. Moreover, in sharing task 2 activity, there were 12 indicators indicating students' highest critical thinking activity of 88.5%. Furthermore, in the jumping task activity, it was found that 9 indicators with students' highest critical thinking activity of 50%. On the other hand, in closing there were 2 indicators with the percentage of 7.7% and 3.8% respectively